Conocimiento didáctico de los profesores de tecnología antecedentes de la investigación - Briceño C., Sergio R. (Revista Científica, 2011)
This article is part of the doctoral thesis “Didactic Knowledge of the content of technology teachers involved in the learning network REDOTIC”, teaching based on knowledge of content, virtual networks for teaching and learning and technological knowledge. The text socializes the academic background of the research conducted in the field of teaching the content knowledge, understanding it as an organizing construct of a cognitive system of knowledge, beliefs, skills, abilities and capabilities. The research aims to characterize the teaching of content knowledge of technology teachers that are part of REDOTIC, from three categories, which are considered as structural: The knowledge of the contents of the object or field of education, it means the disciplinary content knowledge, students ideas and the teaching strategies applied through virtual learning network.